Update on the INTEnsive ambulance-delivered blood pressure Reduction in hyper-ACute stroke Trial (INTERACT4): progress and baseline features in 2053 participants - Chen Chen; Yapeng Lin; Feifeng Liu; Xiaoying Chen; Laurent Billot; Qiang Li; Yiija Guo; Hueiming Liu; Lei Si; Menglu Ouyang; Chunfang Zhang; Hisatomi Arima; et al. (Trials, 2023)
Abstract Background and aims Uncertainty persists over the effects of blood pressure (BP) lowering in acute stroke. The INTEnsive ambulance-delivered blood pressure Reduction in hyper-Acute stroke Trial (INTERACT4) aims to determine efficacy and safety of hyperacute intensive BP lowering in patients with suspected acute stroke. Given concerns over the safety of this treatment in the pre-hospital setting, particularly in relation to patients with intracerebral hemorrhage, we provide an update on progress of the study and profile of participants to date. Methods INTERACT4 is an ongoing multicentre, ambulance-delivered, randomized, open-label, blinded endpoint trial of pre-hospital BP lowering in patients with suspected acute stroke and elevated BP in China. Patients are randomized via a mobile phone digital system to intensive (target systolic BP [SBP] <140mmHg within 30 min) or guideline-recommended BP management. Primary outcome is an ordinal analysis of the full range of scores on the modified Rankin scale scores at 90 days. Results Between March 2020 and April 2023, 2053 patients (mean age 70 years, female 39%) were recruited with a mean BP 178/98 mmHg in whom 45% have a diagnosis of primary intracerebral hemorrhage upon arrival at hospital. At the time of presentation to hospital, the mean SBP was 160 and 170mmHg in the intensive and control groups (Δ10 mmHg), respectively. The independent data and safety monitoring board has not identified any safety concerns and recommended continuation of the trial. The sample size was reduced from 3116 to 2320 after meetings in August 2022 as the stroke mimic rate was persistently lower than initially estimated (6% vs 30%). The study is expected to be completed in late 2023 and the results announced in May 2024. Conclusions INTERACT4 is on track to provide reliable evidence of the effectiveness of ambulance-delivered intensive BP lowering in patients with suspected acute stroke. Trial registration ClinicalTrials.gov NCT03790800 ; registered on 2 January 2019. Chinese Trial Registry ChCTR1900020534 , registered on 7 January 2019.